Kidney as a Target Organ in Cardiac Oncology - Z. D. Mikhailova; D. V. Pivovarov; A. R. Pivovarova (Кубанский научный медицинский вестник, 2020)
The review addresses the problem of kidney lesions in patients with cardiovascular and oncological diseases. In the context of the current spread of cardiovascular and oncological pathologies, a growing number of patients reveal comorbid and/or polymorbid renal dysfunctions. In confluence with cardiovascular disorders, kidney lesions are manifested in various types of the cardiorenal syndrome. In current knowledge, the heart and kidneys are highly interdependent and interact across several interfaces in a complex feedback system. The kidneys can both play a target role and back-influence cardiac functions and pathology. Evidently, the development of acute kidney lesions and / or chronic renal dysfunctions worsens the prognosis of the primary disease and elevates risks of developing acute cardiovascular disorders. Combined cardiovascular and oncological pathologies are nowadays more common. Numerous patients with malignant neoplasms develop renal pathologies due to tumour infiltration or exposure to tumour metabolites, as well as indirectly through the nephrotoxic effect of antitumour chemotherapy and/or radiation therapy. Many studies show that acute kidney lesions and/or chronic renal disorders contribute independently to the severity of cancer and mortality rate. In recent decades, the level of serum creatinine is used as a marker of acute kidney damage, which although harbours inherent weaknesses of being responsive to a spectrum of renal and extra-renal factors and having a delay of 48–72 h of elevation in the blood after exposure to the trigging factor. In this respect, the development of novel kidney-specific lesion biomarkers continues. Among such candidate agents is the kidney injury molecule KIM-1.